Trust, control, interactionand performancein IJVs: A taxonomy of German-Chinese Joint Ventures - Alexander T. Mohr (Universität Duisburg-Essen, Forschungsinstitut für Wirtschaftliche Entwicklungen im Pazifikraum (FIP), 2004)
Control and trust are recurring themes in the analysis of the management of International Joint Ventures (IJVs). Both issues (and their antecedents) have been analysed in isolation and in their relation with performance, though hardly any study exists which analyses them simultaneously in their interdependence. More importantly however, there are few, if any, studies that have empirically tested the existence and nature of the mechanisms that are assumed to link control and trust to performance. It is the purpose of this paper to empirically investigate these mechanisms in view of the interaction processes taking place between the JV partners. Analysing the interaction processes in the context of control, trust and performance is expected to provide a better understanding of the relationship between control, trust and performance. To this aim a concept of inter-firm interaction in IJVs is proposed. The empirical basis for this study consists of data gathered through a questionnaire survey among German and Chinese General Managers of German-Chinese Joint Ventures (GCJVs) in the People?s Republic of China carried out in 2000/01. Using Cluster-Analysis two JV types are derived, which allow for some first yet tentative inferences to be made regarding the complex interplay between control, trust, performance, and interaction in GCJVs.
Keywords: 330; Joint Venture; China; empirical study; trust; control; Internationale Unternehmenskooperation; Joint Venture; Corporate Governance; Management; Vertrauen; Unternehmensentwicklung; Deutschland; China